Economic Convergence in The Integration Process - Slawomir ZWIERZCHLEWSKI1; Katarzyna LASINSKA2; Andrzej PIECZYNSKI2; Rafal KIESZEK2 (Communications of International Proceedings, 2021)
A significant diversity of views on the convergence of the real sphere (real convergence) of the economies of the monetary union (MU) can be demonstrated. Some argue that the extent of real convergence should not be a major obstacle in shaping monetary integration. It is asserted that the phenomenon of real convergence is concerned primarily with the supply dimension and thus should not significantly affect the adjustment processes of the constituent countries of the MU. Opponents of this view assume the existence of differentiated economic potentials in these countries, which may prevent their cooperation within one integration grouping. It seems that in view of the ongoing discussion, it is the latter view that is gaining more approval. More and more often the need to equalize the economic potentials of MU member states is pointed out, which should facilitate the achievement of convergence in other economic spheres.
Keywords: Economic convergence; integration process